Indonesian Beauty Product Customer Experience through Social Media - Ayu Wulandari Septyarini; Asmarsha Qathrinada; Angela Utami Pratiwi; Z Hidayat (Syntax Literate, 2022)
Customer experience greatly determines business success, including beauty care. This study analyzes customer experience when interacting with brands through testimonials published on customers' social media accounts. A qualitative research approach with netnographic methods is used to explore the sharing experience of participants of several brands' beauty care consumers. The dimension of customer experience analysis includes three stages, namely Customer Touchpoint, Moment of Truth, and Customer Involvement. This study indicates that Instagram and YouTube social media campaigns prioritized customer touchpoints. While Moment of Truth is based on customer testimonials, most of which show positive sentiment. Customer involvement reflected through views, likes, and comments has provided customers education about using products, knowing raw materials and manufacturing processes so that customers feel a valuable experience before deciding to subscribe. This study contributes to marketing by utilizing social media technology while inspiring customer experience academically by monitoring public sentiment on social network sites.